The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3917/mana.212.0884
|View full text |Cite
|
Sign up to set email alerts
|

Strategy making as a communicative practice: the multimodal accomplishment of strategy roles

Abstract: We do so by investigating one significant activity within an organizational strategy making process, namely strategy meetings. Here, members of the upper management group create concrete drafts for the actual strategy document, and we focus on a specific action sequence where strategy actors propose changes to the strategy document. Specifically, we investigate how the participants subsequently deal with the proposal, how such interaction work facilitates the accomplishment of strategy roles, and how the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Capturing all these various modes likely requires the close observation of ethnography, supplemented by audio recordings (particularly for talk) and video or photographic recordings (for bodies, material artefacts and space, for example). Thus, Asmuß and Oshima (2018) take a multimodal approach to the detailed study of a management strategy meeting, carefully linking the discourse of managerial interchange to the incremental typing of a strategy document on a notebook computer, its projection onto a whiteboard and the bodily orientations of the Chief Executive Officer (CEO) and his Human Resource manager. The Human Resource manager's pauses at the computer, steady gazes at the CEO and silence in talk all work together to communicate resistance to his superior's proposals.…”
Section: Connecting Streamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Capturing all these various modes likely requires the close observation of ethnography, supplemented by audio recordings (particularly for talk) and video or photographic recordings (for bodies, material artefacts and space, for example). Thus, Asmuß and Oshima (2018) take a multimodal approach to the detailed study of a management strategy meeting, carefully linking the discourse of managerial interchange to the incremental typing of a strategy document on a notebook computer, its projection onto a whiteboard and the bodily orientations of the Chief Executive Officer (CEO) and his Human Resource manager. The Human Resource manager's pauses at the computer, steady gazes at the CEO and silence in talk all work together to communicate resistance to his superior's proposals.…”
Section: Connecting Streamsmentioning
confidence: 99%
“…In particular, practice‐driven institutionalism (Smets et al., 2017) underpins a bridging strategy to connect micro‐praxis and macro‐institutionalism, overcoming micro‐isolationism (Seidl & Whittington, 2014). Multimodal approaches (Asmuß & Oshima, 2018) offer a sequential strategy that adds sociomaterial perspectives to existing discursive ones and addresses urgent questions raised by information technologies and the new virtual world. Critical insights into exclusionary discourse (Vaara, 2010) can be combined with practical managerial concerns via an interplay strategy, with implications especially for intendedly ‘open’ strategy processes (Dobusch & Kapeller, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The external and the internal environments of the firm set limits to the decision process, but the final outcome of decisions is shaped by the top management team (Child, 1997). Several studies have adopted a strategic choice perspective and strategy-as-practice to investigate the effects of the top management team on strategic decision processes (e.g., Asmuß & Oshima, 2018;Elbasha & Wright, 2017;Ericson, 2010;Jansen, Curşeu, Vermeulen, Geurts, & Gibcus, 2011). Other studies, though, have concluded that top management team characteristics may not impact strategic decision processes or that this impact is slight compared to other contextual characteristics (e.g., Lyles & Mitroff, 1980).…”
Section: Top Management Characteristicsmentioning
confidence: 99%
“…In the words of Easterby-Smith (2005, p. 345), it "(is) both for looking at social process over time and for looking at the experiences of those lower down the organizational 'food chain'." It is often difficult to hear the voices of nonstrategic actors (Asmuß & Oshima, 2018). Dynamic observation will be the starting point of emplotment, and enables us to integrate a group of actors into inquiry processes.…”
Section: Limitations and Extensionsmentioning
confidence: 99%